Dynamics behavior of Endoglucanase from Fusarium oxysporum - Noorbatcha, Ibrahim Ali; S., Waesoho; Mohd. Salleh, Hamzah (2011)
Molecular dynamics methods are very useful tool in understanding the behavior of the enzymes at higher temperatures. It is well known that some enzymes lose their enzyme activity at higher temperatures. In this work we employ molecular dynamics simulation of an endoglucanase from Fusarium oxysporum (EGFO) to understand the reasons behind the loss of enzyme activity when the temperatures is increased form 40°C to 80°C. The dynamic behavior of this enzyme is analyzed by examining the Root Mean Square Derivation(RMSD), salt bridges, gyration ratio and hydrogen bonds at different temperatures as a function of time. It has been found that there are differences in (i) the RMSD of backbone and coil regions, (ii) the number of hydrogen bonds among amino acidresidues and between amino acid residues and explicit watermolecules within the coil region of the enzyme (iii) total number of salt bridges, and (iv) the gyration ratio of the enzyme at different temperatures. These factors could play significant role in the loss of activity of EGFO as the temperature is increased.